Communities, universities and ethnicity: A conversation from Imagine: Connecting Communities Through Research. (21st February 2019) - Brown, Milton; Ward, Paul
Abstract : Imagine: Connecting Communities Through Research was a large five-year project in the Connected Communities programme using methodologies of co-production to explore imagining different futures with community groups. This article, which takes the form of a conversation, offers the perspectives of two participants in Imagine to discuss how community organizations and communities work together and the impact of ethnic discrimination and disparity in universities. We set the conversation in the broader context of global discussions of knowledge production and power relationships. We consider how universities, as large institutions, often create difficulties for smaller community organizations by focusing on their own interests. We address power and decision-making in Imagine, especially in relation to ethnicity. We seek to think about what needs to be done, both at strategic levels in universities and on a personal level, to tilt the balance of benefit towards communities in collaborative relationships with higher education institutions.